Mecanismos de prejuízo do relaxamento via endotélio e o estresse oxidativo são revertidos pela atorvastatina em ratas ovariectomizadas - Caliman, Izabela Facco (2012)
The increase in cardiovascular disease (CVD) has been described in postmenopausal women, however there are questions about the use of hormonal therapies as their effectiveness in relation to cardioprotection. Thus estrogen receptor independent therapies, such as atorvastatin, by submitting pleiotropic effects related to the cardiovascular system (CVS), could benefit women in this stage of life, however there are limited data comparing atorvastatin with estrogen on the CVS. So, we performed this study to evaluate the effects of atorvastatin on mesenteric vascular bed (MVB) reactivity from ovariectomized (OVX) female rats, as well as the participation of endothelial relaxing factors on the vascular response. Experiments were performed on female Wistar rats divided into four groups (n=6): control (SHAM); ovariectomized (OVX), OVX treated with 17βestradiol (EST, 0.5µg/Kg/day) and OVX treated with Atorvastatin (ATO, 20mg/Kg/day). Twenty-one days after ovariectomy, the female rats were given the respectively drugs, and those treatments lasted 14 days. At the end of treatment, the MVB was isolated and were conducted dose-response curves to acetylcholine (Ach - 10-12 a 10-3 M) in the presence and absence of blockers for assessment of vascular reactivity. The ovariectomized rats (OVX) showed significant decreases in vasodilator response to ACh under noradrenaline-induced constriction. This decreased response was restored in MVBs obtained from ATO or EST-treated ovariectomized rats. In OVX rats, the relaxation to ACh was significantly reduced by Aminoguanidine, increasing the difference between this group and the SHAM group, indicating an inflammatory process in OVX rats. In presence of L-NAME (10-4 μM) these responses were reduced and equalized, indicating that the initial differences were due to nitric oxide (NO) pathway. The addition of indomethacin (2,8 x 10-6 M) together to the L-NAME did not alter the response obtained with L-NAME alone, showing no significant participation of prostanoids in this response. At same time, there was no difference among groups in the vasodilator response in the presence of clotrimazole (10-6 M), which represents the response mediated by endothelium-derived hyperpolarizing factor (EDHF). Inhibition of reactive oxygen species (ROS), assessed by blocking with ascorbic acid (10-4 M) did not alter the relaxation response observed in control curve, however, inhibition of NADPH oxidase by apocynin (10 -5 M) evoked greater reduction in response to ACh in OVX group than in the others, showing increased oxidative stress in this group, which can be evidenced by the increased production of ROS and increased protein expression of NADPH oxidase in this group. The OVX group also showed lower eNOS expression and increased protein expression of iNOS, while the treatments were able to normalize these values. Furthermore, the OVX group has higher expression of NF-kB, an important transcription factor involved in the inflammatory response, while the ATO were able to reduce this expression. Thus, these data indicate that atorvastatin improved the relaxation dysfunction caused by estrogen deficiency, through mechanisms related to NO pathway, and by reduction in oxidative stress, besides contributing to improvement of the inflammation seen in these animals, providing evidence that non-estrogen therapies could be used to improvement the CVS in estrogen deficient state, such as menopause.